IL-7 suppresses osteogenic differentiation of periodontal ligament stem cells through inactivation of mitogen-activated protein kinase pathway. (1st October 2016) - Jian, Cong-Xiang; Fan, Quan-Shui; Hu, Yong-He; He, Yong; Li, Ming-Zhe; Zheng, Wei-Yin; Ren, Yu; Li, Chen-Jun
ABSTRACT: Periodontal ligament stem cells (PDLSCs) are tissue-specific mesenchymal stem cells (MSCs), having an important role in regenerative therapy for teeth loss. Interleukin-7 (IL-7) is a key cytokine produced by stromal cells including MSCs, and exhibits specific roles for B and T cell development and osteoblasts differentiation of multiple myeloma. However, the effect of IL-7 on osteogenic differentiation of PDLSCs remains unclear. Therefore, in the present study we determined whether IL-7 affects the proliferation and osteogenic differentiation of PDLSCs in vitro and explored the associated signaling pathways for IL-7-mediated cell differentiation. The results demonstrated that the isolated human PDLSCs possessed MSCs features, highly expressing CD90, CD44, CD105, CD29 and CD73, and almost did not expressed CD34, CD45, CD11b, CD14 and CD117. IL-7 could not significantly affect the proliferation of PDLSCs, but it decreased their osteogenic differentiation and inhibited alkaline phosphatase (ALP) activity. The results of quantitative reverse transcription-polymerase chain reaction (qRT-PCR) and Western blotting exhibited that the expression levels of Runx-2, SP7 and osteocalcin (OCN) were significantly reduced by IL-7. Further studies indicated that IL-7 did not significantly change JNK, ERK1/2 and p38 protein production, but markedly suppressed their phosphorylation levels. These data suggest that IL-7 inhibits the osteogenic differentiation of PDLSCs probably via inactivation of mitogen-activated protein kinase (MAPK) signaling pathway.